Robotic Colon and Rectal Surgery : Principles and Practice - Obias, Vincent (Springer International Publishing : Imprint: Springer, 2017)
The initial chapters discuss the start of minimally invasive surgery and robotics. Subsequent chapters address starting up a robotics program and incorporating robotics into ones practice. The textbook next centers on specific robotic techniques or robotic management of certain disease processes. These chapters are written by experts in the fields and include multiple tables, illustrations, and videos describing the techniques where applicable. Each chapter also discusses the current literature. The final chapters focus on the future of robotics, cost of robotics, and include other possible future platforms and as well as the new FDA approved Xi and SP Intuitive surgical platforms. Robotic Colon and Rectal Surgery: Principles and Practice presents the first in-depth, cohesive and comprehensive approach to all aspects of robotic colorectal surgery.
Keywords: Medicine.; Rectum -- Surgery.; elektronické knihy; electronic books